Pengaruh Jarak Penyekat dalam Fotobioreaktor Tubular terhadap Pertumbuhan Kultur Mikroalga Ankistrodesmus convulutus - Chrismadha, Tjandra; Rustiani, Tenni; Rosidah, Rosidah; Mardiati, Yayah (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
A series of partition was constructed inside a vertical tubular photobioreactor to control the culture distribution in obtaining intermittent exposure to light area in the surface of the tubular column. A microalga, Ankistrodesmus convulutus, was grown in a batch mode in the reactor with PHM medium, light sources of fluorescent lamp 3 x 40 watt (I = 5.500 lux on the surface of the tubular) and room temperature of 27 – 310C. The experiment was carried out to study the influence of partition density which was constructed at varied distance, which were 1, 2 and 3 inch on the growth and biochemical composition of the alga. A vertical tubular photobioreactor without partition was applied as the control. The partition density did not significantly affect the optical density achievement of the culture, but it significantly affected the biomass and chlorophyll concentration, as well as the protein/carbohydrate ratio of the culture. It is believed that the intermittent exposure of algal cell to the light area leads to sincronization of the light and dark reaction of the photosynthesis, as well as to vapor the catalitic proccesses to develop the functional cell structure.